Organic-inorganic hybrids prepared by carboxylic acid solvolysis: Planar waveguides - Molina, C.; Maia, L. J. Q.; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Elsevier B.V., 2012)
Organic-inorganic hybrid planar waveguides based on the UV sensitive methacryloxypropyltrimethoxysilane (MAPTMS) were prepared through non-hydrolytic sol-gel process by carboxylic acid solvolysis and also containing the fluormonomer precursor 2,2,3,3-tetrafluorpropylmethacrylate (TFPM) and methacrylic acid (MA) modified zirconium alkoxide (ZPO). The absence of water and the incorporation of C-F bonding containing precursor contributed to obtain low optical loss in the final material. Characterization techniques included Si-29-NMR, vibrational spectroscopy and optical characterization of the, waveguides with measurements of refractive index, thickness, propagating modes and attenuation coefficient by m-lines prism coupling technique at 632.8, 543.5 and, 1550 nm were performed. The surface of the films was investigated by roughness (RMS) and contact angle measurements. (c) 2011 Elsevier B.V. All rights reserved.
Keywords: Waveguides; Sol-Gel; Hybrids; Fluormonomer precursor; Solvolysis